The Relationship between the Level of Corruption and Economic Growth in Indonesia: An Investigation using Supply Chain Strategy and Bounds Test - Antoni Antoni; Ridzuan Masri; Abdul Murad Bin Ahmad; Irwan Muslim; Nasfi Nasfi; Sabri Sabri; Rahmad Rahmad (International Journal of Supply Chain Management, 2019)
Global competition has intensified geographic repositioning of supply chain activities with implications for the economic prosperity of specific regions and geographies affected by such shifts. This study examines the relationship between the level of corruption and economic growth using the supply chain and ARDL bounds test method. The data used are GDP, the level of corruption, foreign direct investment, government spending and inflation from 2000-2018. The results of the study indicate a negative and significant impact on the level of corruption on economic growth in the long run. The implication of this research is that weak institutions, indicating the failure of government (corruption) that affect the performance of economic growth.